2012
DOI: 10.1016/j.worlddev.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Converting Asset Holdings into Livelihood: An Empirical Study on the Role of Household Agency in South Africa

Abstract: This paper analyzes the complexities of converting assets into livelihood and the role that agency constraints play. Drawing inspiration from the capabilities approach and using household data from South Africa, linkages between assets and agency are identified by decomposing asset endowments' impact on future livelihood. By employing a method of path analysis akin to early heritability of traits studies, theoretical asset-based studies of chronic poverty are bridged with capabilities literatures. The interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Adult unemployment is a growing concern in South Africa, especially in KwaZuluNatal Province (Anderson 2012). This is due both to a lack of employment opportunities and to absolute poverty caused by limited employable skills among adults (Soobramoney 2011).…”
Section: Theoretical Framework For Internal Enabling Of Nfet Environmmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult unemployment is a growing concern in South Africa, especially in KwaZuluNatal Province (Anderson 2012). This is due both to a lack of employment opportunities and to absolute poverty caused by limited employable skills among adults (Soobramoney 2011).…”
Section: Theoretical Framework For Internal Enabling Of Nfet Environmmentioning
confidence: 99%
“…However, poverty increased more than expected in the postapartheid period due to unemployment among non-educated and unskilled adults (Anderson 2012;May 2010). Committed to redressing the historical lack of education and training and promoting lifelong learning, the South African government legislated non-formal adult education and training through the Adult Education and Training (AET) Act 25 of 2010.…”
Section: Introductionmentioning
confidence: 98%
“…However, poverty due to unemployment among non-educated and unskilled adults has increased more than was expected in the post-apartheid period (Anderson 2012;May 2010). To redress the historical lack of education and training and promote lifelong learning, the South African government legislated NFET through the Adult Education and Training (AET) Act 25 of 2010 (RSA 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has addressed several aspects of NFET, including the examination of the relevance of NFET for income generation (Islam et al 2012;Blaak et al 2012); acquisition of practical skills (Georgiadou et al 2009;Islam et al 2012); socioeconomic empowerment of adults who are poor (Morton and Montgomery 2011;Akpama et al 2011); the ineffectiveness of NFET; and skills mismatch in terms of supply and demand on the labour market (Morton and Montgomery 2011;Anderson 2012). Research has shown that NFET centres and their adult trainees continue to experience challenges due to the insufficiency of enabling environments (DHET 2012;Aitchison 2007;Blaak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Adults are active labour force participants, but their entry into labour markets is hindered by a lack of education and skills impediments (World Bank, 2004). In South Africa particularly, a lack of education and training among poor adults is a significant contributor to unemployment and poverty (Anderson, 2012). This is due to absolute poverty caused by limited employable skills among adults on the one hand and on the other the lack of employment opportunities in the KwaZulu-Natal province where the study was conducted (Soobramoney, 2011).…”
Section: Introductionmentioning
confidence: 99%